The association between anxiety, daily behaviors, and insomnia among university students - Dita Anisa Ismardi; Edlin Edlin; Yolanda Eliza Putri Lubis; Radhitya Qowiyyul Davin; Muhammad Raihan Ishak; Hendy Million; Rudolf Alponso; Jansen Jansen (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Insomnia is a common problem among university students and is often associated with psychological factors such as anxiety and modifiable daily behaviors. This study aimed to examine the relationships between anxiety levels, specific daily habits (including caffeine consumption, physical activity, and academic stress), and the occurrence of insomnia among students aged 20 to 25 years at Universitas Prima Indonesia. Methods: An observational analytic study with a cross-sectional design was conducted in May 2025. A total of 94 students participated as respondents. Data were collected using structured questionnaires, including the Hamilton Anxiety Rating Scale (HAM-A) and the Insomnia Severity Index (ISI). The chi-square test was applied to analyze the associations between variables. Results: Most respondents were female (61.7%) with a mean age of 21.21 years. Descriptive analysis showed trends suggesting that higher anxiety and physical activity levels were associated with increased insomnia rates. However, statistical analysis revealed no significant relationship between anxiety and insomnia (p = 0.203) or between physical activity and insomnia (p = 0.190). In contrast, caffeine consumption showed a statistically significant association with insomnia severity (p = 0.006). Conclusion: Although anxiety and physical activity were not significantly related to insomnia in this study, caffeine consumption was identified as a significant modifiable risk factor. These findings emphasize the need for targeted health education programs to improve sleep hygiene among students, particularly by addressing caffeine intake to enhance sleep quality.